Pengaruh Waktu Tahan pada Perlakuan Panas Pasca Pengelasan terhadap Kekerasan dan Kuat Tarik Baja Karbon ASTM A106 Grade B - M. Nizar Machmud; Defri Maulana; - Husaini (Jurnal Teknik Mesin Unsyiah, 2013)
Experimental investigations to study significant effects of employing a post weld heat treatment (PWHT) technique on mechanical properties of the welded carbon steel have been performed. This paper presents a study on hardness and tensile strength characteristics of a carbon steel A106 grade B welded using shielded metal arc welding (SMAW) method with employing normalizing procedures. With the PWHT technique, heating temperature of the steel, that was set up to 850°C, was then maintained for these following set of holding times: 10, 20 and 30 minutes before cooling. Heating and cooling rates of the carbon steel were also slowly maintained. Investigation results under tension showed that the tensile strength of the carbon steel decreased with increase of the holding time. The best tensile strength was achieved by the carbon steel treated with a holding time for 20 min. Toughness of the carbon steel under tension is also discussed in order to correlate the influence of employing the PWHT technique on their fracture modes. Investigation with Vickers hardness test showed that the Vickers hardness on weld metal, weld line, heat-affected zone (HAZ) and base metal of the welded carbon steel, respectively, decreased and tended to be equivalent with the increase of the holding time.